Three new steroidal sapogenins derived from the roots of Cynanchum otophyllum and their cytotoxic activities. (October 2021) - Li, Xiao-San; Yang, Xue-Mei; Liu, Li; Zhang, Meng; Ren, Yi-Chang; Zhan, He-Hui; Xing, Rui; Luo, Rong-Rong; Chen, Tang-Ji; Tang, Jin-Shan
Graphical abstract: Highlights: Three new steroidal sapogenins (1-3 ) were isolated from the roots of Cynanchum otophyllum . Compound 1 harbouring a rare beta -OH at the C-8 position in the cardenolide skeleton. Compound 1 showed the strongest cytotoxicity with IC50 of 6.86–22.09 μM. Abstract: Three new steroidal sapogenins, 3 β, 8 β, 14 β -trihydroxycarda-5, 20(22)-dienolide (1 ), (20 R )-12 β, 20-epoxy-3 β, 8 β, 14 β -trihydroxy-17 α -pregn-5-en-17-yl 4-hydroxy-3-methoxybenzoate (2 ), and 3, 20-dioxo-8 β, 14 β, 17 β -trihydroxy-17 α -pregn-5-en-12 β -yl 4-hydroxybenzoate (3 ), along with four known C21 -steroidal sapogenins (4-7 ) were isolated from the hydrolysate of Cynanchum otophyllum roots. Among them, compound 1 harbouring a rare β- OH at the C-8 position in the cardenolide skeleton, was identified for the first time in the genus Cynanchum . Their structures were elucidated via extensive spectroscopic analysis, including UV, IR, HR-ESI-MS, 1D and 2D NMR. Compounds 1-7 were evaluated for their cytotoxic activities against four cancer cell lines (MCF-7, H1299, HeLa, and HepG2). Compound 1 exhibited significant inhibitory effects on the growth of the four cell lines, exhibiting IC50 values ranging from 6.86 to 22.09 μM.